2018
DOI: 10.1016/j.jlp.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational Fluid Dynamics study of separation gap effect on gas explosion mitigation for methane storage tanks

Abstract: This paper presented both experimental and numerical assessments of separation gap effect on vented explosion pressure in and around the area of a tank group. A series of vented gas explosion layouts with different separation gaps between tanks were experimentally investigated. In order to qualitatively determine the relationship between the separation gap distance and explosion pressure, intensive computational Fluid Dynamics (CFD) simulations, verified with testing data, were conducted. Good agreement betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Additionally, it can also be observed that the P ex in FLACs increases as early as 0.71 ms. According to Li et al(Li et al, 2018), this phenomena occurred due to the high initial burning rate of flame in FLACs simulation which was also reported by Ma et al (2014) and Pedersen and Middha (2012).…”
Section: Methodssupporting
confidence: 66%
“…Additionally, it can also be observed that the P ex in FLACs increases as early as 0.71 ms. According to Li et al(Li et al, 2018), this phenomena occurred due to the high initial burning rate of flame in FLACs simulation which was also reported by Ma et al (2014) and Pedersen and Middha (2012).…”
Section: Methodssupporting
confidence: 66%
“…Also, they calculated the resulting pressure and deformation. Lee et al [26,27] examined the blast pressure inside and outside the space of the water tanks. They presented the calculation procedure for the internal and external pressures in the water tanks.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al assessed effects on vented explosion pressure in and around the area of a tank group. For their research, they designed a series of tank layouts with different separation gaps [20,21] and calculated the internal and external pressures subjected to different separation gaps. ey also proposed equations for calculating the tank's pressure-time history duration and shape.…”
Section: Introductionmentioning
confidence: 99%